Modeling Techniques in Group Counseling to Improve Student Learning Discipline and Self-Control - Putra, Dedy; Hastuti, Maria (Psikopedagogia, 2021)
This study aims to test the effectiveness of group counseling with modeling techniques in improving 11th grade students’ learning discipline and self-control in SMA Muhammadiyah 3 Yogyakarta. This experimental study involved fourteen students recruited using the purposive sampling technique. The data collection used is a scale of learning discipline and self-control. The data analysis technique used in this study was non-parametric statistics with the Man Withney (U) test and the Wilcoxon test using the SPSS 20.0 for windows. The results of the Wilcoxon test showed that: (1) the modeling technique was effective in increasing the learning discipline of class XI students (sign = 0.018<0.05) and (2) the modeling technique was effective in increasing self-control in class XI students (sign = 0.018<0, 05) The results of the Wilcoxon test show that the modeling technique group counseling service is effective in improving learning discipline and self-control in class XI students of SMA Muhammadiyah 3 Yogyakarta. The results of the Mann Whitney test showed that: (1) the modeling technique was effective in increasing the learning discipline of class XI students (sign = 0.002 <0.05) and (2) the modeling technique was effective in increasing self-control in class XI students (sign = 0.002 <0 ,05) The results of the Mann Whitney test show that the modeling technique group counseling service is effective for improving learning discipline and self-control for class XI students at SMA Muhammadiyah 3 Yogyakarta. The results of this study can be used as a recommendation for BK teachers as an alternative to providing counseling services for students related to learning discipline and self-control, so that students have good learning discipline and self-control.